Information Technology as a Basis for the Development of Multicultural Islamic Education Institutions - Lilik Nur Fadhilah; M Djunaidi Ghony; Masykuri Bakri (Syntax Idea)
information and communication has opened a new chapter for the public to obtain information autonomously. Information barriers are automatically opened by the strong desire of individuals who always want to know the lates information regarding any matter. The development of education that is increasingly contemporary and the demands of todays era cannot be denied, marked by the rapid development of information technology. Which has produced significant changes. Therefore, information technology as a basis for the development of multicultural Islamic education institutions is very important if implemented, because it will make it easier for institutions to move forward. We use this opportunity as a golden opportunity for institutional development. The research used is qualitative. Information technology is very useful for institutional development, namely the existence of institutional content, utilizing the media as an integrated data bank for each division, as a media teamword, providing a special website for new student registration, and having a special institutional website to facilitate user access.